Lymphocyte predominant cells detect Moraxella catarrhalis-derived antigens in nodular lymphocyte-predominant Hodgkin lymphoma - Thurner, Lorenz; Hartmann, Sylvia; Fadle, Natalie; Regitz, Evi; Kemele, Maria; Kim, Yoo-Jin; Bohle, Rainer Maria; Nimmesgern, Anna; von Müller, Lutz; Kempf, Volkhard A. J.; Weniger, Marc A.; Neumann, Frank; et al. (Nature communications, 2020)
Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is a rare lymphoma of B-cell origin with frequent expression of functional B-cell receptors (BCRs). Here we report that expression cloning followed by antigen screening identifies DNA-directed RNA polymerase beta’ (RpoC) from Moraxella catarrhalis as frequent antigen of BCRs of IgD + LP cells. Patients show predominance of HLA-DRB1*04/07 and the IgVH genes encode extraordinarily long CDR3s. High-titer, light-chain-restricted anti-RpoC IgG1/κ-type serum-antibodies are additionally found in these patients. RpoC and MID/hag, a superantigen co-expressed by Moraxella catarrhalis that is known to activate IgD + B cells by binding to the Fc domain of IgD, have additive activation effects on the BCR, the NF-κB pathway and the proliferation of IgD + DEV cells expressing RpoC-specific BCRs. This suggests an additive antigenic and superantigenic stimulation of B cells with RpoC-specific IgD + BCRs under conditions of a permissive MHC-II haplotype as a model of NLPHL lymphomagenesis, implying future treatment strategies. Nodular lymphocyte-predominant Hodgkin lymphoma with IgD+ lymphocyte-predominant (LP) cells is a rare clinical distinct lymphoma subset of B-cell origin. Here the authors show that antigens expressed by Moraxella catarrhalis are recognized by B cell receptors of IgD+ LP cells, suggesting the contribution of chronic antigen stimulation to lymphomagenesis.